Presence of diadenosine polyphosphates in microdialysis samples from rat cerebellum in vivo: effect of mild hyperammonemia on their receptors - Gualix, Javier (Springer Netherlands, 2013)
Diadenosine triphosphate (Ap(3)A), diadenosine tetraphosphate (Ap(4)A), and diadenosine pentaphosphate (Ap(5)A) have been identified in microdialysis samples from the cerebellum of conscious freely moving rats, under basal conditions, by means of a high-performance liquid chromatography method. The occurrence of Ap(3)A in the cerebellar microdyalisates is noteworthy, as the presence of this compound in the interstitial medium in neural tissues has not been previously described. The concentrations measured for the diadenosine polyphosphates in the cerebellar dialysate were (in nanomolar) 10.5 ± 2.9, 5.4 ± 1.2, and 5.8 ± 1.3 for Ap(3)A, Ap(4)A, and Ap(5)A, respectively. These concentrations are in the range that allows the activation of the presynaptic dinucleotide receptor in nerve terminals. However, a possible interaction of these dinucleotides with other purinergic receptors cannot be ruled out, as rat cerebellum expresses a variety of P2X or P2Y receptors susceptible to be activated by diadenosine polyphosphates, such as the P2X1-4, P2Y(1), P2Y(2), P2Y(4), and P2Y(12) receptors, as demonstrated by quantitative real-time PCR. Also, the ecto-nucleotide pyrophosphatases/phosphodiesterases NPP1 and NPP3, able to hydrolyze the diadenosine polyphosphates and terminate their extracellular actions, are expressed in the rat cerebellum. All these evidences contribute to reinforce the role of diadenosine polyphosphates as signaling molecules in the central nervous system. Finally, we have analyzed the possible differences in the concentration of diadenosine polyphosphates in the cerebellar extracellular medium and changes in the expression levels of their receptors and hydrolyzing enzymes in an animal model of moderate hyperammonemia. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11302-013-9382-3) contains supplementary material, which is available to authorized users.